2020
DOI: 10.1177/1053451220910733
|View full text |Cite
|
Sign up to set email alerts
|

Combining Universal Design for Learning and Self-Regulated Strategy Development to Bolster Writing Instruction

Abstract: Students with disabilities encounter persistent barriers in writing, which manifest within all phases of the writing process. These challenges can involve both higher order processes (e.g., organization, idea development) as well as lower order processes (e.g., legibility, spelling) related to writing. Educators can apply the principles of the universal design for learning (UDL) to lesson design by prioritizing student engagement considerations, promoting increased options for composing writing, and representi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Absent discussion and demonstration of how teachers might simultaneously implement multiple evidence-based approaches to best support students, practitioners risk viewing the collection of instructional HLPs as a list of skills to be practiced in isolation rather than in concert with each other. Although McClesky and colleagues (2019) clearly advocate for the need to combine effective practices, such as HLPs, educators must see examples of how such combinations might be applied in classroom-based scenarios to increase the chances they will incorporate both practices into their teaching (Hashey et al, 2020).…”
Section: Both Explicit Instruction (Ei) and Universalmentioning
confidence: 99%
See 1 more Smart Citation
“…Absent discussion and demonstration of how teachers might simultaneously implement multiple evidence-based approaches to best support students, practitioners risk viewing the collection of instructional HLPs as a list of skills to be practiced in isolation rather than in concert with each other. Although McClesky and colleagues (2019) clearly advocate for the need to combine effective practices, such as HLPs, educators must see examples of how such combinations might be applied in classroom-based scenarios to increase the chances they will incorporate both practices into their teaching (Hashey et al, 2020).…”
Section: Both Explicit Instruction (Ei) and Universalmentioning
confidence: 99%
“…It does not need to be utilized in isolation and is not incompatible with research-validated methodologies in special education. For example, Hashey et al, (2020) offer specific practice-based means of utilizing self-regulated strategy development within a UDL framework to optimize access to content and, in turn, leverage learning outcomes. Next, we highlight key elements of EI and illustrate how these elements can be enhanced when implemented through a UDL lens.…”
Section: Udlmentioning
confidence: 99%
“…The multiple means of engagement principle of the UDL framework refer to the encouragement and enhancement of motivation among students while cultivating enthusiasm for learning [ 36 ]. There are numerous theories of motivation including attribution theory [ 37 ], social cognitive theory [ 38 ] and self-determination theory [ 39 ] which form the basis of student motivation questionnaires such as the Motivated Strategies for Learning Questionnaire (MSLQ) [ 40 ], used in the current study, to assess the self-reported academic motivation of students, including students in higher education [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Snow (2018) demonstrated how to vitalize student assessments by taking inspiration from UDL. It has been reported that UDL allowed students to explore various teaching and learning methods (Katz & Sokal, 2016), and therefore have the opportunity to learn to work in an optimal manner (Hashey et al, 2020). Implementing UDL in a third level public health program demonstrated an increase in learning, student engagement, improved personal development and student experience (Shiely & McCarthy, 2019).…”
Section: Introductionmentioning
confidence: 99%